Right heart catherisation – a virtual reality. (3rd October 2022) - Brown, M; Krishnananthan, N; Paul, V
Abstract: Introduction: Right heart catheterisation (RHC) is the gold standard for assessing patients with pulmonary hypertension. Doctors require training in this procedure in a safe and friendly environment with minimal risk to patients. Due to the Covid pandemic, formal RHC teaching workshops were cancelled in our country, so we sought to develop a Virtual Reality Right Heart Catheterisation (VRRHC) training program to fulfil this area of need without the need for face to face contact. The aim was to improve training, competency and confidence in this technique with improved diagnostic skills and reduction of procedural errors. Method: We approached a health technology company to design a VRRHC training module based on our current RHC simulation workshops. Phase 1 required virtual insertion of RHC via the right internal jugular vein using micro-puncture, double Seldinger technique under ultrasound guidance, followed by insertion of the RHC to the right atrium, right ventricle and pulmonary artery with pulmonary artery occlusion using real time pressure tracings and fluoroscopy. Thermodilution cardiac outputs and chamber saturations were also performed. The proprietary platform technology was delivered via a laptop and VR headset. Clinicians perform the VRRHC with imaging, monitoring and haptic feedback with the collection of real time performance tracking allowing user data (e.g. failed steps and proficiency scores) to be captured and subsequently visualised in the learning management system. We collected analytics and data on user engagement, experience and retention, targeted learning outcomes and learning curve, reduction in operating costs, reduction in procedure times due to higher proficiency, early diagnosis of pulmonary hypertension, reduced complications, improved interpretation and diagnosis. Results: The program was launched in October 2021. Preliminary data shows a learning curve is associated with both using VR (10–15 minutes) and the RHC procedure itself. Initial time to completion of the RHC was 30–40 mins, reducing to 20–30 minutes with experience and 15 minutes in experts. Completion rates increase with experience from 40–50% to 100% and error rates reduce with frequency of completion. Conclusion: A Virtual Reality Right Heart Catheter training program is safe, feasible and non-invasive. Increased experience results in increased completion rates, reduced procedure time and reduced errors. Using this program will potentially have beneficial effects on doctor training, outcomes, patient safety and health economics with no risk to a real patient. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Janssen Pharmaceuticals